Ox-cart man - Hall, Donald, 1928-2018.; Cooney, Barbara, 1917-2000. (New York : Viking Press, 1979)
Describes the day-to-day life throughout the changing seasons of an early 19th-century New England family.
Keywords: Caldecott Medal; New England -- Fiction